Activating Concentrated Curiosity in Problem Construction to enhance Creative Problem Solving - Greenblatt, Jennifer (University of the Witwatersrand, Johannesburg, 2024)
As the first stage in the creative problem solving process, problem construction plays a pivotal role in facilitating the creativity of solutions generated. This thesis develops a theory that proposes an approach to optimise two sub-stages of problem construction, namely, the information search and problem framing, and subsequently builds a normative framework based on this theory to provide practical, evidence-based guidelines to improve the effectiveness of creative problem solving in organisations. To date, research into approaches to search for information about the problem has received little attention, and approaches to effectively frame a problem prior to generating solutions are still debated. Furthermore, research findings have not been leveraged to inform an evidence-based normative framework. This thesis comprises four papers. In paper one, the theory is developed based on literature research. In paper two, the theory is tested experimentally by exposing four groups of senior managers in a large financial services company to different experimental conditions and then comparing the creativity of solutions generated using two different approaches to the information search and two different approaches to problem framing. The development of a normative framework in paper three draws on both the theory and experimental findings. In this paper, in-depth interviews are also conducted with problem solvers from various disciplines to test the applicability and relevance of the framework developed to address the information search. The effectiveness of this normative framework is tested in an action research study in paper four, and findings are used to refine the framework and implementation guidelines. This study also serves as a second field test of the theoretical model.
A research report submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Creative Problem Solving; Problem construction; Problem framing; Information Search; Creativity; Innovation; SDG-17: Partnerships for the goals